Integration of Russian speakers in the Baltic states (Economic and Political Thought, 2017)
The aim of the article is to investigate comparatively integrationpolicies of Estonia, Latvia and Lithuania as well as adaptation strategies ofRussian-speakers in the Baltic states following the Baltic states’ independence.As a result, existing integration approaches, their determinants and effectswill be outlined. In addition, the study addresses the issue of shaping civicand cultural identities of Russian speaking residents as a result of integrationprocesses. The analysis is based on the assumption that the Baltic states haveused different integration models as a consequence of various historical,political and social factors. The effectiveness of the integration process hasdepended on both the national strategy and the openness of the (titular andminority) ethnic groups to adaptation in the new environment.